1997
DOI: 10.1037/0096-3445.126.1.19
|View full text |Cite
|
Sign up to set email alerts
|

A time course analysis of Stroop interference and facilitation: Comparing normal individuals and individuals with schizophrenia.

Abstract: Using randomized stimulus onset asynchrony (SOAs), the authors traced the time course of Stroop interference and facilitation in normal participants and participants with schizophrenia. Unlike earlier findings using blocked SOAs, singular peaks in interference, facilitation, or both occurred at particular SOAs. The peaks of normal participants and participants with schizophrenia differed. Findings are congruent with a model of Stroop performance that posits individual differences in processing speeds of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
60
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 43 publications
11
60
0
Order By: Relevance
“…For instance, deficits of executive function such as distractibility, perseverance and failure to inhibit irrelevant responses may reflect an inability to utilise WM (Park et al 1999). Pertinent to this, schizophrenic patients are similarly impaired on a wide range of tasks, such as the Continuous Performance Task (Buchsbaum et al 1990), the Wisconsin Card Sort Test (Goldman-Rakic and Selemon 1997), the Stroop Test (Schooler et al 1997), the Tower of London Task (Andreasen et al 1992), and on oculomotor delayed-response paradigms (Park and Holzman 1992;Pierrot-Deseilligny et al 1993). These tasks have in common that they require WM (Goldman-Rakic and Selemon 1997), which is in accordance with the possibility of a basic role of WM in schizophrenic cognitive deficits, although it is still conceivable that certain cognitive deficits occur independently of a WM deficit.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, deficits of executive function such as distractibility, perseverance and failure to inhibit irrelevant responses may reflect an inability to utilise WM (Park et al 1999). Pertinent to this, schizophrenic patients are similarly impaired on a wide range of tasks, such as the Continuous Performance Task (Buchsbaum et al 1990), the Wisconsin Card Sort Test (Goldman-Rakic and Selemon 1997), the Stroop Test (Schooler et al 1997), the Tower of London Task (Andreasen et al 1992), and on oculomotor delayed-response paradigms (Park and Holzman 1992;Pierrot-Deseilligny et al 1993). These tasks have in common that they require WM (Goldman-Rakic and Selemon 1997), which is in accordance with the possibility of a basic role of WM in schizophrenic cognitive deficits, although it is still conceivable that certain cognitive deficits occur independently of a WM deficit.…”
Section: Introductionmentioning
confidence: 98%
“…One explanation is that, through a lifetime of practice, reading has become so automatized that it impacts processing, even under color-naming instructions (Cohen, Dunbar, & McClelland, 1990). Other theories include response compatibility (Dalrymple-Alford & Azkoul, 1972), differential translation requirements (Virzi & Egeth, 1985), and speed of processing (Schooler, Neumann, Caplan, & Roberts, 1997). Evaluating these explanations often involves identifying and testing qualitative predictions they make.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that patients exhibit increased RT facilitation (congruent RT vs. neutral RT) compared with healthy controls rather than increased RT interference (incongruent RT vs. neutral RT), as often inferred from studies employing card versions of the Stroop (Barch et al, 1996;Carter, R0bertson, & Nordahl, 1992;Carter, Robertson, Nordahl, O'ShoraCelaya, & Chaderjian, 1993;Cohen, Barch, Carter, & Servan-Schreiber, in press;Schooler, Neuman, Caplan, & Roberts, 1997;Taylor, Kornblum, & Tandon, 1996). However, in single-Wial studies, patients show increased interference as reflected in error rates rather than RT.…”
mentioning
confidence: 99%